2007
DOI: 10.1007/s11120-007-9219-4
|View full text |Cite
|
Sign up to set email alerts
|

Photoproduction of hydrogen by sulfur-deprived C. reinhardtii mutants with impaired Photosystem II photochemical activity

Abstract: Photoproduction of H2 was examined in a series of sulfur-deprived Chlamydomonas reinhardtii D1-R323 mutants with progressively impaired PSII photochemical activity. In the R323H, R323D, and R323E D1 mutants, replacement of arginine affects photosystem II (PSII) function, as demonstrated by progressive decreases in O2-evolving activity and loss of PSII photochemical activity. Significant changes in PSII activity were found when the arginine residue was replaced by negatively charged amino acid residues (R323D a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…This observation is important because it is opens up a way to improve the H 2 production in green algae, which is based on enhanced respiratory reactions, similar to Stm6 and some other mutant systems (23,27,39). The search for existing mutations or engineering of new ones, which can create earlier and extended anaerobic conditions, will potentially overcome two major problems.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is important because it is opens up a way to improve the H 2 production in green algae, which is based on enhanced respiratory reactions, similar to Stm6 and some other mutant systems (23,27,39). The search for existing mutations or engineering of new ones, which can create earlier and extended anaerobic conditions, will potentially overcome two major problems.…”
Section: Discussionmentioning
confidence: 99%
“…Sulfate permease mutants had a phenotype similar to that of sulfur-deprived wild-type algae and produced H 2 at similar levels (Chen et al 2005). A different approach focused on the feasibility of using D1 mutants with reported lower O 2 evolution capability as H 2 -producers in closed photobioreactors (Makarova et al 2007). Unfortunately, the specific mutants used in this study were unable to over-accumulate starch, a sine-qua-non for efficient H 2 photoproduction during anaerobiosis.…”
Section: Photosynth Resmentioning
confidence: 99%
“…This has been used to propose that the low residual PSII activity is the predominant H 2 production pathway during S deprivation. It has been estimated that about 90-60 % of H 2 production is PSII-dependent Fouchard et al 2005;Hemschemeier et al 2008;Antal et al 2009Antal et al , 2011, and that the PSII centers that remain active during the anaerobiosis phase (Makarova et al 2007;Antal et al 2011;Volgusheva et al 2013) contribute to sustain the H 2 production observed during S deficiency.…”
Section: Photosynth Resmentioning
confidence: 99%